The Representation of Women in Pakistani Television Dramas: Analyzing the Preservation of Social Norms (Journal of Asian Development Studies, 2025)
The representation of women in Pakistani television dramas is a major influence on how society perceives gender roles. This study explores whether this representation upholds cultural norms or challenges them. Using a mixed-method approach, content and thematic analysis of two selected dramas, Sar-e-Rah (2023) and Durr-e-Shehwar (2012), was conducted to evaluate the portrayal of traditional roles, female agency, empowerment, and subjugation. The result illustrates that Durr-e-Shehwar upholds conventional gender norms by portraying women in submissive, domestic, and dependent roles, reinforcing patriarchal expectations. Female characters in this drama are depicted as self-sacrificing individuals whose primary roles revolve around family obligations. In contrast, Sar-e-Rah presents a more progressive representation, showcasing women as independent decision-makers who challenge societal norms. The drama highlights female agency and empowerment themes, mainly through its protagonist, who defies traditional expectations by taking control of her life and career. The study establishes that Pakistani dramas significantly shape audience attitudes toward women by reinforcing or challenging societal norms. While some dramas offer narratives promoting self-sufficiency and personal autonomy, unfortunately, most provide narratives beholden to traditional structures. This unproportional dual representation creates conflicting messages about women's roles in society. The findings suggest that the media should strive for balanced narratives that reflect cultural realities and encourage gender equality and empowerment rather than propagating limiting stereotypes.